Upstairs/Downstairs: Moving up and down through leadership roles - Markus Pomper; Margaret Thomas Evans (Academic Chairpersons Conference Proceedings, 2022)
The presenters will discuss the challenges they encountered moving up from department chair into the role of dean and associate dean, and the back down into the role of a chair. We will engage participants through interactive discussion in several case studies.
Keywords: Transitioning roles; career changes; academic leadership